Author Correction: Two-magnon scattering in the 5d all-in-all-out pyrochlore magnet Cd2Os2O7. Issue 1 (December 2017) - Nguyen, Thi; Sandilands, Luke; Sohn, C.; Kim, C.; Wysocki, Aleksander; Yang, In-Sang; Moon, S.; Ko, Jae-Hyeon; Yamaura, J.; Hiroi, Z.; Noh, Tae
A correction to this article has been published and is linked from the HTML version of this article.